2020
DOI: 10.1021/acsbiomaterials.0c00295
|View full text |Cite
|
Sign up to set email alerts
|

Control of Matrix Stiffness Using Methacrylate–Gelatin Hydrogels for a Macrophage-Mediated Inflammatory Response

Abstract: The successful tissue integration of a biomedical material is mainly determined by the inflammatory response after implantation. Macrophage behavior toward implanted materials is pivotal to determine the extent of the inflammatory response. Hydrogels with different properties have been developed for various biomedical applications such as wound dressings or cell-loaded scaffolds. However, there is limited investigation available on the effects of hydrogel mechanical properties on macrophage behavior and the fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 55 publications
(98 reference statements)
5
59
0
Order By: Relevance
“…As shown, the content of F-actin rose after CMIMP addition (p < 0.001) (Figure 2E,F). Comparing with the undifferentiated macrophages, the content and microfilament spreading area of F-actin is increased in M1 cells [26]. In line with that, macrophages were induced into M1 phenotype by CMIMP [19].…”
Section: Cmimp Enlarged the Size And F-actin Expression Of Macrophagessupporting
confidence: 73%
“…As shown, the content of F-actin rose after CMIMP addition (p < 0.001) (Figure 2E,F). Comparing with the undifferentiated macrophages, the content and microfilament spreading area of F-actin is increased in M1 cells [26]. In line with that, macrophages were induced into M1 phenotype by CMIMP [19].…”
Section: Cmimp Enlarged the Size And F-actin Expression Of Macrophagessupporting
confidence: 73%
“…Several studies have indicated an effect of substrate stiffness on macrophage behaviour. Although the studied stiffnesses and compositions of the substrates varied greatly, stiffening of the substrate is generally associated with more macrophage adhesion and a bigger and more flattened phenotype as compared to a smaller and more rounded shape on soft substrates [71–82]. Nonetheless, these observed morphological changes on two‐dimensional (2D) substrates may not be fully translatable to an in vivo situation.…”
Section: Macrophage Responses To Biophysical Changesmentioning
confidence: 99%
“…The effect of substrate stiffness on pro‐inflammatory or profibrotic responses of macrophages has also not yet been shown conclusively. Most studies indicated more pro‐inflammatory behaviour when substrate stiffness increased, based on the expression of markers such as IL‐1β, IL‐6, and TNF‐α [75,78,80,81,83,88,89], although the opposite has also been described [77,82,87,90]. However, these studies all investigated short‐term responses of macrophages to substrates of various stiffnesses.…”
Section: Macrophage Responses To Biophysical Changesmentioning
confidence: 99%
“…Therefore, bone biomaterials with favorable immunoregulation properties could create the anticipated immune niches and stimulate the secretion of osteogenic and osteoclast cytokines in bone regeneration process. [ 46–48 ]…”
Section: Introductionmentioning
confidence: 99%